PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN PADA PRODUK BUAH NAGA DI DESA TOTTONG KECAMATAN DONRI-DONRI KABUPATEN SOPPENG - Sari, Sri Puspita; Mustari, Mustari; Supatminingsih, Tuti; Said, Muh. Ihsan; Dinar, Muhammad (Politeknik Negeri Lhokseumawe, 2024)
Abstract: The aim of this research is to determine the effect of product quality and promotion on consumer satisfaction through purchasing decisions as an intervening variable for dragon fruit products in Tottong Village, Donri-Donri District, Soppeng Regency. The method used is a quantitative approach. The population in this study was consumers of dragon fruit products in Tottong Village whose population was unknown, and in determining the sample using the Cochran formula a sample size of 97 people was obtained, which was taken using a non-probability sampling method with accidental sampling technique. The data collection technique used in this research used a list of questions/questionnaire. Data analysis techniques in this research use Path Analysis, Classic Assumption Test, Hypothesis Test (t Test and f Test), Correlation Analysis and Coefficient of Determination. Data processing in this research used IBM SPSS software program version 26. This research resulted in findings that: (1) product quality significantly influences consumer satisfaction with Dragon Fruit products in Tottong Village, (2) promotion significantly influences consumer satisfaction with Buah Naga products Dragon in Tottong Village, (3) product quality significantly influences purchasing decisions for Dragon Fruit products in Tottong Village, (4) promotions significantly influences purchasing decisions for Dragon Fruit products in Tottong Village, (5) consumer satisfaction does not significantly influence purchasing decisions on Dragon Fruit products in Tottong Village, (6) purchasing decisions as an intervening variable cannot mediate between product quality and consumer satisfaction on Dragon Fruit products in Tottong Village, (7) purchasing decisions as an intervening variable cannot mediate between promotion and satisfaction consumers of Dragon Fruit products in Tottong Village.Keywords: Product Quality, Promotion, Consumer Satisfaction, Purchasing Decisions